KERJA SAMA KEPOLISIAN REPUBLIK INDONESIA DAN POLIS DIRAJA MALAYSIA DALAM MENANGGULANGI PEREDARAN NARKOBA DI KEPULAUAN RIAU TAHUN 2017-2021 - Septiari Aulia Handayani Tanjung (2023)
The level of drug trafficking in Indonesia and Malaysia is increasingly high,the caused is the strategic position of Indonesia and Malaysia which are close to the Golden Triangle in Myanmar.The Riau Archipelago is a direct border area between Indonesia and Malaysia and often used an entry for drug traffickers between the two countries.This study aims to discuss the collaborative efforts of the Indonesian National Police (POLRI) with the Royal Malaysian Police (PDRM) in tackling drug trafficking in the Riau Archipelago during 2017 - 2021. Qualitative-descriptive method is used in this research. The theory for this research based on theory of International Cooperation and the concept of Transnational Crime. Meanwhile, the data used in this study are secondary data derived from journals, articles, and other sources related to this research problem.